GAMBARAN LUAS RUANGAN REKAM MEDIS DI UPTD PUSKESMAS SUMBER - Nur Liya; Loura Weryco Latupeirissa; Eka Martaviantika Gusana (Jurnal Kesehatan Mahardika, 2020)
The distance between the aisle shelves in the medical record file storage space must meet the requirements for easy retrieval and maintenance. The total area of the room is adjusted to the needs assessment. The purpose of this study was to determine the distance between the storage shelves in Sumber Public Health Center, to know the needs of shelves for medical records file Sumber Public Health Center and to know the description of the medical record room in Sumber Public Health Center. This type of research is a descriptive method. The object of this research was the area of medical record room in Sumber Public Health Center, but to determine the average thickness of BRM in supporting the calculation of room size requirements the size of the sample used was 396 BRM. Sampling in this research is using random sampling with group sampling. The instruments used in this study used measuring aids (meters and micrometers), calculating aids, the formula for storing medical records and observation guidelines The results of this study are the distance between the passageways of the storage shelves at Sumber Public Health Center at the moment, which is 48 cm, the storage rack needs to store 46,353 medical records files as many as 9 shelves and the current medical record space at the Sumber Public Health Center is 5.74 m2. Based on the results of the measurement of the need for a room of medical records is 9.60 m2 so it requires the addition of 3.86 m2 of space. Thus the need for space is not sufficient because the needs of the current storage rack still requires the addition of storage racks so that it is also needed to increase the storage space. Puskesmas are expected to add more storage space for medical records or can switch to electronic medical records.